2022
DOI: 10.31248/ijet2022.138
|View full text |Cite
|
Sign up to set email alerts
|

Perception of secondary school science and mathematics teachers on Professional development participation in Zamfara State, Nigeria

Abstract: The study adopted a descriptive survey design to examine the perception of secondary school science and mathematics teachers on professional development in Zamfara State, Nigeria. The population of the study consisted of all Science and Mathematics teachers in public secondary schools in Zamfara State. A sample of 217 respondents were drawn through purposive and simple random sampling techniques. Data were collected using a structured questionnaire. Four research questions and two null hypotheses guided the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Therefore, every science "and mathematics teacher", both new and experienced, requires training at some point in order to improve their performance (Eboka & Mbanefo, 2022). This buttressed the assertion of Sodangi et al, (2022) that, to effectively manage the dynamic demands of students, science and mathematics teachers require rigorous and continuous re-training through various forms of professional development not only outside but also within school level.…”
Section: Throughmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, every science "and mathematics teacher", both new and experienced, requires training at some point in order to improve their performance (Eboka & Mbanefo, 2022). This buttressed the assertion of Sodangi et al, (2022) that, to effectively manage the dynamic demands of students, science and mathematics teachers require rigorous and continuous re-training through various forms of professional development not only outside but also within school level.…”
Section: Throughmentioning
confidence: 99%
“…However, despite the fact that discussions and interactions between principals and teachers about school-related issues are common in the school system (Kotirde & Yunos, 2014), yet, research findings have revealed that there is a significant gap between what teachers receive in the form of professional development and what they hope to receive (Sodangi et al, 2022;Westberry & Horner, 2022). For instance, Sodangi et al, (2022) reported lack of principals" support for science and mathematics teachers" professional development in Zamfara State. Hence suggested the need for principals to keep encouraging teachers under their leadership to keep abreast of new knowledge and skills through collaboration, mentoring, coaching etc.…”
Section: Throughmentioning
confidence: 99%
See 3 more Smart Citations